Cortical Abnormalities in Epilepsy Revealed by Local EEG Synchrony - Schevon, C. (2007)
Abnormally strong functional linkage between cortical areas has been postulated to play a role in the pathogenesis of partial epilepsy. We explore the possibility that such linkages may be manifest in the interictal EEG apart from epileptiform disturbances or visually evident focal abnormalities. We analyzed samples of interictal intracranial EEG (ICEEG) recorded from subdural grids in nine patients with medically intractable partial epilepsy, measuring interelectrode synchrony using the mean phase coherence algorithm. This analysis revealed areas of elevated local synchrony, or “hypersynchrony” which had persistent spatiotemporal characteristics that were unique to each patient. Measuring local synchrony in a subdural grid results in a map of the cortical surface that provides information not visually apparent on either EEG or structural imaging. We explore the relationship of hypersynchronous areas to the clinical evidence of seizure localization in each case, and speculate that local hypersynchrony may be a marker of epileptogenic cortex, and may prove to be a valuable aid to clinical ICEEG interpretation.